10-14 yaş kız ve erkek türk badmintoncularının fiziki gelişim ve fiziki uygunluk parametrelerinin değerlendirilmesi - Özgür, Beyhan (My University, 2010)
EVALUATION OF THE PHYSICAL DEVELOPMENT AND PHYSICAL FITNESS PARAMETERS OF THE TURKISH FEMALE AND MALE BADMINTON PLAYERS OF 10-14 AGE Beyhan ÖZGÜR In this study, in the result of the investigation of the physical development and physical fitness parameters of the Turkish female and male badminton players of the age group of 10 – 14 and in the result of the obtained data, the comparison with the other studies of the literature was aimed. 171 male badminton players of average age of 12.05±1.21 and 139 female badminton players of average age of 12.27±1.24 from 35 provinces of all over of Turkey participated in the research. The investigation was done in the Turkey interschools championship of Stars and Little badminton players, as well as in the championship of Turkey under the ages of 9-11-13. Height, stroke length, body weight measurements, 20 m sprint test, standing long jump, vertical jump, flexibility (the deep bending) throwing of medicine ball of 2 kgs and back strength tests were performed and applied to the athletes. In addition, as the result of these applications, the anaerobic power of the athletes and the body mass index values were calculated. The obtained data was transferred to the SPSS 14 packet program and together with this program, Descriptives Tests (standard deviation, minimum, maximum, average) were used for its descriptive statistics, the Independent-Samples T test was used for comparing of the difference between the sexes, the One-Way ANOVA test was used for comparing of the difference between the age groups, and the person correlation test was used for investigation of the relationship between the physical fitness parameters. As a result, badminton players participated in the survey, sprint, standing long jump, vertical jump, back strength values are low, anaerobic power values were higher. Key words: Badminton, evaluation, physical development, physical fitness
Keywords: Beden Eğitimi ve Spor; Fiziki Gelişim